Dakwah Politik Haji Agus Salim - Sendi Ramadhan; Lia Pediati; Murodi; Syamsul Yakin (IAIN Madura, 2024)
This research focuses on the political preaching of Haji Agus Salim, who was a charismatic cleric and accomplished diplomat who fought to defend Indonesia's sovereignty in the international arena. The aim of this research is how Haji Agus Salim's political preaching is, by presenting information about the biography, works, thoughts, and political preaching movements of Haji Agus Salim. Using qualitative descriptive methods. The results obtained in this writing are that Haji Agus Salim has a fairly long life track record in the history of the Indonesian struggle, his intelligence and skill in debating are known throughout the country, and his ability to master foreign languages ​​made him very popular among the Dutch government at that time. Haji Agus Salim is also listed as one of the Indonesian independence fighters who was later nicknamed The Grand Old Man. Haji Agus Salim carries out political da'wah through his works, starting from his writings and his ideological understanding of aqidah and syariah. His political da'wah movements can be seen from his participation in Sarekat Islam and the founding of the Jong Islamieten Bond and Volksraad to his heroism in Indonesian independence.